2002
DOI: 10.1515/znc-2002-9-1024
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating Effect of Mizoribine on the Anti-Herpes Virus Activity of Acyclovir

Abstract: Pharmacological induction of low deoxyribonucleoside triphosphate (dNTP) levels in virus-infected cells could result in an increased antiviral effectiveness of some selective antiviral nucleoside analogues. That could be exploited as a new combined strategy in the treatment of herpes virus infections. From this point of view the alteration of antiherpes activity of acyclovir (ACV) in combination with mizoribine (N′-[β-d-ribofuranosyl]-5-hydroxyimidazole-4-carboxamide) (MZR), an inhibitor which lowers the intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Diversity among the nucleotide sequences of SFTSV strains reported from China, Japan, and South Korea is less than 5z (5,6), which suggests that ribavirin would likely show similar inhibitory effects against all SFTSV strains, regardless of areas from where the viruses have been isolated. Although both ribavirin and mizoribine have been shown to inhibit several viruses including herpes simplex virus, respiratory syncytial virus, influenza virus, and severe acute respiratory syndrome virus (17)(18)(19)(20), mizoribine did not show an efficient inhibitory effect on SFTSV proliferation. The finding that effective doses of ribavirin against SFTSV were higher in Vero cells than in the other 2 cell lines (Table 1) is consistent with previous reports by Huffman et al (25) and Peters et al (23), in which the impact of ribavirin on several DNA/RNA viruses was compared in several cell lines.…”
mentioning
confidence: 90%
“…Diversity among the nucleotide sequences of SFTSV strains reported from China, Japan, and South Korea is less than 5z (5,6), which suggests that ribavirin would likely show similar inhibitory effects against all SFTSV strains, regardless of areas from where the viruses have been isolated. Although both ribavirin and mizoribine have been shown to inhibit several viruses including herpes simplex virus, respiratory syncytial virus, influenza virus, and severe acute respiratory syndrome virus (17)(18)(19)(20), mizoribine did not show an efficient inhibitory effect on SFTSV proliferation. The finding that effective doses of ribavirin against SFTSV were higher in Vero cells than in the other 2 cell lines (Table 1) is consistent with previous reports by Huffman et al (25) and Peters et al (23), in which the impact of ribavirin on several DNA/RNA viruses was compared in several cell lines.…”
mentioning
confidence: 90%
“…Both studies, however, show good antivirus activity of acyclovir in combination with mizoribine. It was established that there is a synergistic combined effect of acyclovir and mizoribine on the replication of strain CapHV-1 (Elia et al, 2015, Camero et al, 2017 and on the human HSV-1 (Pancheva et al, 2002). In these previous experiments, acyclovir was used in sub-inactive concentrations, and with the addition of mizoribine a strong synergistic effect was obtained.…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that mizoribine 5′-monophosphate acts as an inhibitor of inosine 5′-monophosphate dehydrogenase (IMPDH) and guanosine monophosphate synthetase [8]. In addition, mizoribine is known to inhibit replication of some DNA and RNA viruses, such as cytomegalovirus [9], respiratory syncytial virus [10], severe acute respiratory syndrome-associated coronavirus (SARS-CoV) [11], bovine viral diarrhea virus (BVDV) [12], vaccinia virus [13], influenza virus types A and B, and herpesviruses, in combination with acyclovir [14,15]. However, the antiviral activity of mizoribine against FMDV has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%